Telaah Hukum Ekonomi Islam Terhadap Pendapatan Istri Dalam Meningkatkan Kesejahteraan Keluarga - Nurul Azizah Azzochrah; Abdul Wahab; Saleh Ridwan (DIKTUM: Jurnal Syariah dan Hukum, 2019)
This research is entitled Study of Islamic Economics Against Wife Income in Improving Family Welfare (Case Study in Manggala Sub-District, Manggala Sub-District, Makassar City). This study describes how the financial role of the family and how Islam views wives who work? To obtain answers from the expected, the author uses three methods of data collection; Observations, interviews and documentation. Processing data using qualitative data with data analysis techniques used by the author are; Data reduction, data presentation and data verification. The sample in this study was the wife who worked in the Manggala sub-district of Manggala District, Makassar City. The results of this study indicate that the income accounted for for families and families with multiple careers in the Manggala sub-district based on BPS measurements includes the welfare family. In Islam there is no prohibition for women to work outside who violate the rules of Islamic law, the work of women is contrary to the principles of Islamic economics, namely ta'awun and maslahat